Benefits of Working in Pairs in Problem Solving and Algorithms - Action Research - Soly Mathew Biju (Athens Institute for Education and Research, 2019)
The purpose of this study is to examine the impact of peer tutoring program as compared to classroom tutoring on problem solving and algorithm development skills of higher education students in Computer Sciences. Peer tutoring has emerged as one of the most effective mechanisms of enabling learning and improving academic performance of students at all levels of education. It has since been put into practice by various institutions in a number of ways involving the tutor, the tutee and teachers or school administration who work together through a systematic process. Peer tutoring has emerged as one of the most effective mechanisms of enabling learning and improving academic performance of students at all levels of education. Primary research where selected students were trained and assigned peer tutees in the algorithms and problem solving class taught to undergraduates in the first semester. Students were placed in pairs. A pair consists of a peer tutor selected based on certain criteria and a tutee. The interesting aspect of this study is that it tests the impact of working in pairs had a positive impact on both on the tutor and the tutee